Multi-channel silicone rubber traps as denuders for gas–particle partitioning of aerosols from semi-volatile organic compounds. Issue 5 (5th April 2017) - Kohlmeier, Vesta; Dragan, George C.; Karg, Erwin W.; Schnelle-Kreis, Jürgen; Breuer, Dietmar; Forbes, Patricia B. C.; Rohwer, Egmont R.; Zimmermann, Ralf
Abstract : Multi-channel silicone rubber traps represent a new approach towards gas–particle partitioning of aerosols from semi-volatile organic compounds. Abstract : During many measurements it is important to account for possible changes in the gas–particle distribution of aerosols containing semi-volatile organic compounds (SVOCs). If denuders are combined with currently used personal air samplers, a simultaneous differential sampling of the gas and particle phase is possible. Here we analysed the transmission efficiency of denuders based on multi-channel silicone rubber traps (setup: 9 cm long glass liner (ID 4 mm), containing 22 parallel silicone rubber tubes (55 mm long, ID 0.3 mm, OD 0.5 mm)) with polystyrene latex (PSL) particles for different scenarios. n -Hexadecane, dimethyl phthalate and diethylene glycol gases were used to measure the time-dependent gas phase collection efficiency of a denuder. Additionally, the evaporation of n -hexadecane aerosol particles passing through the denuders was investigated. Our results showed high transmission efficiencies from 91 to 100% (variation coefficients 3.69–9.65%) for the denuders operated vertically at a flow rate of 0.5 l min −1 . With regard to the gas phase collection efficiency, nonpolar n -hexadecane gas was trapped with higher efficiency (87% after 22 h) than dimethyl phthalate gas (27% after 22 h), while for highly polar diethylene glycol the gas phase collection efficiency was 50% after 2 h. Regarding the evaporation of aerosol particles, smaller particles and lower flow rates led to higher particle volume reduction inside the denuders. In conclusion, the tested denuders are suitable for determining the gas–particle partitioning of SVOC aerosols of nonpolar substances and show above 90% transmission for all tested particle sizes.